(untitled) (International Journal of Physiology, 2019)
Background Peak Expiratory Flow Rate (PEFR) reflects the strength and condition of respiratory muscles and the degree of airflow limitation in large airways. PEFR shows postural variation that follows a specific pattern in asthmatics and healthy individuals has been identified. Adequate data is not available for the postural variation in normal individuals who are students in professional courses and had a sedentary life style. Lung volumes in normal subjects were significantly higher in standing position. Others have reported that in healthy subjects spirometric indices were higher in the standing in comparison with the sitting position whereas other studies have reported no differences between spirometric values obtained in lying, sitting and standing positions. Hence this study is undertaken to study the postural variation in peak expiratory flow rates in healthy adult female subjects in South India. Method Peak expiratory flow rate was recorded in 50 adult healthy female students aged 18–23 years and studying in professional courses. Mini wright’s peak flow meter was used to measure the peak expiratory flow rate. Three readings were taken PEFR in standing and lying posture. Best of three recordings taken as the final value. Results PEFR is decreased in lying posture compared to standing posture in subjects studied and the quantum of difference was noted. Conclusion In postural changes, peak expiratory flow rate measurements significantly differ based on whether the measurements are taken in the standing or in the lying posture in healthy participants. The effect of posture may be of importance in recording peak expiratory flow rate and changing to a better posture may be especially useful for those patients with weak expiration.